AB0053 CD20+CD27+CD43+CD70-Cells, Proposed as Human B-1 Cells Are Increased in Systemic Lupus Erythematosus, But Not Correlated with Disease Activity. (9th June 2015) - Kang, S.E.; Yoo, H.J.; Park, J.K.; Kim, T.J.; Oh, H.J.; Joo, S.H.; Lee, J.M.; Lee, S.J.; Kim, K.R.; Lee, E.Y.; Lee, E.B.; Song, Y.W.
Abstract : Background: Systemic lupus erythematosus (SLE) is an autoimmune disease characterized by the production of multiple autoantibodies by hyperactive B cells. B-1 cells distinguished from conventional B cell, perform a protective role in defending against microbial pathogens by secreting natural antibodies. Recently, human B-1 cells identified phenotypically according to the characterization of murine B-1 cells, were reported to be increased in peripheral blood of SLE patients. Objectives: The aim of this study is to investigate the frequency of B-1 cells and its correlation with disease activity in SLE. Methods: Peripheral blood mononuclear cells were isolated from 21 SLE patients and 16 age/sex matched healthy controls. Frequencies of B-1 cells were analyzed by multicolor flow cytometry using antibodies against CD3, CD20, CD27, CD43, and CD70. Phenotype of human B-1 cells was identified by CD3 - CD20 + CD27 + CD43 + CD70 - . Correlation of B-1 cell frequency with the disease activity of SLE was analyzed according to anti-dsDNA antibody, complement level, renal involvement, platelets count, white blood cell count, erythrocyte sedimentation rate (ESR), and SLE disease activity index (SLEDAI) score. Results: Absolute B cell count was significantly decreased in SLE patients compared to healthy controls (mean ± SE: 29813±8096 cells/ml vs. 62593±10465 cells/ml, p =0.002). Frequencies of B-1 cell in total B cells were significantly increased in SLE patients compared to healthy controls (1.86±0.33 vs. 0.79±0.10, p =0.025). SLE patients with anti-dsDNA antibody tended to have higher frequency of B-1 cells than patients without anti-dsDNA antibody (1.92±0.39 vs. 1.77±0.60). However there was no correlation between complement level, renal involvement, platelets count, white blood cell count, ESR, or SLEDAI score and B-1 cell frequency. Conclusions: The frequencies of B-1 cell were significantly higher in SLE compared to healthy controls. But there was no correlation between disease activity and B-1 cell frequency. References: Griffin DO, Holodick NE, and Rothstein TL. Human B1 cells in umbilical cord and adult peripheral blood express the novel phenotype CD20 + CD27 + CD43 + CD70 - . J. Exp. Med 2011;208:67-80. Griffin DO, and Rothstein TL. Human B1 cell frequency: isolation and analysis of human B1 cells. Front. Immunol. 2012;3:122. Tørring C, Petersen CC, Bjerg L, et al. The B1-cell subpopulation is diminished in patients with relapsing-remitting multiple sclerosis. J Neuroimmunol. 2013;262:92-99. Disclosure of Interest: None declared